Investigation the adaption of pea (Pisum sativum) Lines and varieties under Mediterranean climatic conditions - Dürdane, Mart; Türkeri, Meltem (CEP USM, 2024)
This research was conducted in Adana ecological conditions of the Eastern Mediterranean region in order to determine the yield and yield components of pea genotypes that were advanced in the breeding studies carried out in Adana province during the 2022-2023 growing period. The experimental material consisted of 20 genotypes and 3 commercial varieties considered as control. The experiment was carried out according to the randomized block design with three replications, 45 cm between rows, 10 cm above rows, 5 m in length and 4 rows (5mX4 rowsX0,45m) for each genotype. The sowing of the experiment was carried out on December 20, 2022 for winter and the harvest was completed on June 5, 2023. According to the results of the research findings, the flowering period of the varieties varied between 67.50-58 days, pod setting period 79.50-70 days, plant height 182.50-57cm, first pod height 68-23.50cm, hundred grain weight 28.85-11.24gr and grain yield 245-105.33kgda. According to the data obtained at the end of the research, Adana1, Adana3, Adana8, Adana13, Adana14, Adana15 and Adana16 genotypes, which have high values in terms of grain yield and hundred grain weight, were found suitable for evaluation for the region and recorded in breeding studies. However, in order to make a better decision, it should be supported by more long-term and detailed agronomic studies.
Keywords: pea; yield; quality and yield parameters